ブライド ワン ト セールロンダーネ サンチ カン ノ ヒョウショウ チケイ - 西尾, 文彦; ニシオ, フミヒコ; 石川, 正雄; イシカワ, マサオ; 大前, 宏和; オオマエ, ヒロカズ; 高橋, 修平; タカハシ, シュウヘイ; 勝島, 尚美; カツシマ, タカヨシ; Nishio, Fumihiko; Ishikawa, Masao; et al. (1984)
P(論文) 1983年2月12日から17日の期間, 第23次および第24次南極地域観測隊は, セールロンダーネ山地における本格的な地球科学的調査の予備調査として, ブライド湾からセールロンダーネ山地の間の氷河地形学的調査を行った。その結果と過去のベルギー隊の得た結果を併せて下記のような推論を行った。ブライド湾からセールロンダーネ山地の間の氷床は, セールロンダーネ山地によって内陸からのクィーンモードランド氷床流が阻止され, 理論的に示される平衡氷床高度分布より著しく低く, セールロンダーネ山地の溢流氷河の涵養量は少ない。ブライド湾周辺の棚氷の縁辺の形状は, 1960年作成のベルギー隊の地図とほとんど変化がなく, 同一形状の棚氷の位置の変位から棚氷の移動速度を求めると, 北方へ56-126m/aであった。1967年から1973年の間に旧ロア・ボードワン基地と棚氷の前縁との間に大きな断裂帯が形成されていたが, その原因は不明である。将来, この断裂帯が広くなり, ブライド湾の棚氷は氷山となって分離していく可能性が考えられる。ブライド湾とセールロンダーネ山地の間の氷床の質量収支を近似的に求めた結果, この氷床の涵養源の一部は, 現在の大量の積雪量であることが推定される。もし, 現在の積雪量が著しく減少し, 氷床表面高度の低下が発生すると, 氷床の厚さが減じて現在の接地線(grounding line)が後退するであろう。そして, 氷床が氷山となって分離していく速さを加速するであろう。なぜならば, 氷床底面は内陸深くセールロンダーネ山地近くまで海面下に位置すると考えられるからである。問題をはっきりさせるためには, 氷床基盤の調査が重要である。 During the period from 12 to 17 February 1983,a preliminary study of glacial geomorphology was carried out in the area between Breid Bay and the Sør Rondane Mountains by the 23rd and 24th Japanese Antarctic Research Expedition to implement earth science programs in the Sør Rondane Mountains. The obstruction by the Sør Rondane Mountains to the ice flow is the cause of the elevated ice surface in the south of the mountains, and also the cause of the extremely low level in the north of the mountains, probably aided by the shelter effect of the mountains. Outlines of the ice shelf front and the respective positions have indeed remained unchanged over twenty-three years, but the reentrant, a widely and deeply fractured zone, is formed in the ice shelf between the Base Roi Baudouin and the ice front. It was found that the reentrant was formed between 1967 and 1973,and further fracturing of the platform of this ice shelf may occur with the development of crevasses, and therefore the ice shelf may break off in not so far future. A rough estimate of the mass budget of the ice sheet in the area between Breid Bay and the Sør Rondane Mountains suggests that the ice sheet may keep the present shape owing to the high accumulation rate over the ice sheet surface at present. If the present accumulation rate ...